Merger of Trading Companies, a Chance of Salvation During the Crisis - Anca-Simona Hromei (CES Working Papers, 2013)
Mergers are transactions often used as growth strategies by companies that are trying to gain a competitive advantage, or in order to fulfil their objectives. In this period, marked by uncertainty and risk, mergers can be an effective way to enhance the competitive power on the market, or a way to save, restore the declining companies. Given the emphasis on mergers in recent years, this article tries to offer a theoretical approach on mergers, with a highlight on the conceptual framework and the advantages that can be obtained by mergers. Some advices that any manager should take into consideration before completing the merger and, also, in the afterwards period, in order to ensure the success of this process, are presented.
Keywords: M41; G34; 330; mergers; financial performance; advantages of mergers; success Romania